1998
DOI: 10.1021/bi980504y
|View full text |Cite
|
Sign up to set email alerts
|

Global Conformational Changes upon Receptor Stimulation in Photoactive Yellow Protein

Abstract: Biological signal transduction starts with the activation of a receptor protein. Two central questions in signaling are the mechanism of activation by a stimulus and the nature and extent of the protein conformational changes involved. We report extensive evidence for the occurrence of large structural changes upon the light activation of photoactive yellow protein (PYP), a eubacterial photosensor. Absorption of a blue photon by the p-coumaric acid (pCA) chromophore in pG, the initial state of PYP, results in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
143
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 126 publications
(159 citation statements)
references
References 45 publications
15
143
1
Order By: Relevance
“…3). This dispersed distribution is in line with the partially unfolded nature of the pB state (25)(26)(27)(28)(29): Its decay involves refolding of many regions of the protein, and can thus be affected by mutations at many different locations. The statistically significant correlation of 0.59 between ΔG U and τ pB in the Ala scan dataset (Table S4) supports a link (25) between protein folding and pB decay.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…3). This dispersed distribution is in line with the partially unfolded nature of the pB state (25)(26)(27)(28)(29): Its decay involves refolding of many regions of the protein, and can thus be affected by mutations at many different locations. The statistically significant correlation of 0.59 between ΔG U and τ pB in the Ala scan dataset (Table S4) supports a link (25) between protein folding and pB decay.…”
Section: Resultssupporting
confidence: 57%
“…Photoexcitation causes the conversion of the initial pG dark state of PYP into the long-lived pB state. The pB state has a blueshifted absorbance spectrum and is partially unfolded (25)(26)(27)(28)(29). Its formation involves dissociation of the N-terminal region from the core of PYP (30,31).…”
mentioning
confidence: 99%
“…The structure of PYP without the first 25 residues (termed ⌬25PYP) in the pB state has recently been investigated by NMR experiments (41) and parallel tempering molecular dynamics (MD) simulations (42). This structure is consistent with spectroscopic studies [FTIR (32), NMR (35,43,44), H/D exchange (37,45), fluorescence (46), and circular dichroism (40)] of the pB state in aqueous solution. That is, PYP partially unfolds its PAS domain during the photocycle, and this may be a key process in its signaling function (47).…”
Section: Background On the Photoactive Yellow Protein Systemmentioning
confidence: 63%
“…1A). Because it has been demonstrated that PYP exposes hydrophobic contact surface when it is present in the pB state (28,29) and pH indicators might bind to such sites, similar measurements were performed in a solution buffered with 50 mM MES buffer (pH 6.0). Fig.…”
Section: Resultsmentioning
confidence: 99%